2007
DOI: 10.1159/000106494
|View full text |Cite
|
Sign up to set email alerts
|

Altered Urinary Release of Inositol Phosphoglycan A-Type in Women with Gestational Diabetes Mellitus

Abstract: Background/Aims: The mechanisms underlying overgrowth of adipose tissue in fetuses of women with gestational diabetes mellitus (GDM) are generally unknown. Inositol phosphoglycan A-type (A-IPG), a putative second messenger of insulin, was reported to regulate lipogenesis in adipose tissue. IPGs have recently been shown to increase during normal pregnancy, in maternal and fetal compartments. Methods: 48 women with GDM and 23 healthy pregnant women were recruited for this cross-sectional study. Levels of A-IPG w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The effects of GDM on urinary excretion of free MI and DCI in the present study differ to those reported for urinary elimination of inositol-containing phosphoglycans in fasting urine samples from late pregnancy. In GDM, urinary excretion of DCI-IPG at 26 to 30 weeks’ gestation was significantly greater than the value for normal pregnancy, 28,29 and the average urinary elimination of MI-IPG was significantly lower than the mean for normal pregnancy. 28 However, caution should be exercised when drawing a comparison to our study.…”
Section: Discussionmentioning
confidence: 65%
“…The effects of GDM on urinary excretion of free MI and DCI in the present study differ to those reported for urinary elimination of inositol-containing phosphoglycans in fasting urine samples from late pregnancy. In GDM, urinary excretion of DCI-IPG at 26 to 30 weeks’ gestation was significantly greater than the value for normal pregnancy, 28,29 and the average urinary elimination of MI-IPG was significantly lower than the mean for normal pregnancy. 28 However, caution should be exercised when drawing a comparison to our study.…”
Section: Discussionmentioning
confidence: 65%
“…The same authors observed a positive association between DCI urinary excretion and poor glycaemic control in the second trimester of pregnancy . On the contrary, they observed that a poorer glycaemic control resulted in a reduction on Myo urinary content . The authors argue that increased DCI production/excretion, as well as the reduced Myo urine content, could represent a compensatory reaction to the hyperinsulinaemic state, rather than a primary effect mediated by insulin resistance.…”
Section: Inositol Molecular and Metabolic Aspectsmentioning
confidence: 95%
“…In addition, inositol (either in the DCI or MI isoform) has been reported to mediate glucose uptake by improving insulin sensitivity. Insulin‐mimetic effects of MI or its isomers seem to be derived from inositol phosphoglycan (IPG) which contains MI or DCI 13 . IPG acts as a second messenger in insulin signaling pathways and plays a vital role in the activation of enzymes involved in glucose uptake and utilization 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Insulin-mimetic effects of MI or its isomers seem to be derived from inositol phosphoglycan (IPG) which contains MI or DCI. 13 IPG acts as a second messenger in insulin signaling pathways and plays a vital role in the activation of enzymes involved in glucose uptake and utilization. 14 Different rates of IPG imbalance have been observed in patients with diabetes and obesity.…”
Section: Introductionmentioning
confidence: 99%